RESEARCH ON SUGAR BEET PRODUCTION AND TRADE -WORLDWIDE OVERVIEW - Elena SOARE; Iuliana DOBRE; Livia DAVID (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The research highlights aspects of the production and commercialization of sugar beet at the worldwide level. The analysis is considering 2012-2019 based on specific indicators relating production and commercialization of sugar beet. The statistical data used in this research were taken from the FAO. The most representative indicators analyzed in the study refers to the areas cultivated with sugar beet worldwide, total sugar beet production, average production per hectare of sugar beet and imports and exports of sugar beet. According to the data, Europe is the largest producer of sugar beet in the world. In this context, Europe obtained over 60% of the sugar beet production registered worldwide with different uses. Globally, sugar made from sugar beet has only 20% of sugar production. The difference in production obtained worldwide is made from sugar cane.